2012
DOI: 10.1016/j.ufug.2012.06.006
|View full text |Cite
|
Sign up to set email alerts
|

A systematic quantitative review of urban tree benefits, costs, and assessment methods across cities in different climatic zones

Abstract: Urban trees can potentially mitigate environmental degradation accompanying rapid urbanisation via a range of tree-benefits and services. But uncertainty exists about the extent of tree benefits and services because urban trees also impose costs (e.g. asthma) and may create hazards (e.g. windthrow). Few researchers have systematically assessed how urban tree benefits and costs vary across different cities, geographic scales and climates. This paper provides a quantitative review of 115 original urban tree stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
461
0
30

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 848 publications
(492 citation statements)
references
References 136 publications
1
461
0
30
Order By: Relevance
“…Urban areas are steadily growing throughout the world (Grimm et al 2008) and by 2030 it is expected that 60% of the world's population will be living in cities (Rydin et al 2012). Thus, as urban environments become more important as living space for humans, they are an increasing source of carbon emissions.Several studies in North America, China, and Australia (Brack 2002;Zhao et al 2010;Dobbs et al 2011;Martin et al 2012;Roy et al 2012), and more recently in the United Kingdom and Germany (Davies et al 2011;Strohbach & Haase 2012;Strohbach et al 2012), have shown that trees in urban environments remove carbon dioxide from the atmosphere through growth and photosynthesis, and store excess carbon as biomass in roots, stems, and branches. Indirectly, urban trees also reduce building energy used for cooling through their shade and climate amelioration effects, thereby reducing CO 2 emissions from decreased energy production (Akbari et al 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Urban areas are steadily growing throughout the world (Grimm et al 2008) and by 2030 it is expected that 60% of the world's population will be living in cities (Rydin et al 2012). Thus, as urban environments become more important as living space for humans, they are an increasing source of carbon emissions.Several studies in North America, China, and Australia (Brack 2002;Zhao et al 2010;Dobbs et al 2011;Martin et al 2012;Roy et al 2012), and more recently in the United Kingdom and Germany (Davies et al 2011;Strohbach & Haase 2012;Strohbach et al 2012), have shown that trees in urban environments remove carbon dioxide from the atmosphere through growth and photosynthesis, and store excess carbon as biomass in roots, stems, and branches. Indirectly, urban trees also reduce building energy used for cooling through their shade and climate amelioration effects, thereby reducing CO 2 emissions from decreased energy production (Akbari et al 2001).…”
mentioning
confidence: 99%
“…Similarly, tree growth is influenced by genetics, climate, soil, moisture, light, and competition (Peper & McPherson 1998;Bühler et al 2007). These effects on tree growth and mortality are well-known in European forests, but the majority of studies of urban trees growth rates have been conducted in the United States of America (USA) (Jo & McPherson 1995;Iakovoglou et al 2002;Lawrence et al 2012;Roy et al 2012). We know only a few studies on urban tree mortality and growth in northern Italy (Sanesi et al 2007;Semenzato et al 2011;Marziliano et al 2013), but no studies providing information specific to urban tree growth rates in South Tyrol, Italy, are known to us.…”
mentioning
confidence: 99%
“…To provide an example, urban forests are being widely used as NBS and generally considered as important to mitigate several weather related hazards -they keep the temperature down during heat waves, they can stabilize soils and help in preventing flooding (Roy et al 2012;Livesley et al 2016). However, despite this wide recognition of value, the fact that urban forests themselves may be vulnerable to the same disturbances is less recognised.…”
Section: The Role Of Diverse Ecosystemsmentioning
confidence: 99%
“…These themes have been emphasized by many authors who stress the negative side effects of changes in climatic conditions (Brown et al, 2015;Demuzere et al, 2014;Gill et al, 2007;Byrne et al, 2015;Mathews et al, 2015;Byrne & Young, 2009;Foo et al, 2015). Today the urban environment is reported to be under threat from many environmental problems: floods, storm waters, winds, and urban heat (Mathews et al, 2015;Brown et al, 2015;Demuzere et al, 2014;Beer, 2010.;Bowler et al, 2010;Roy et al 2012;Jim et. al., 2015) are having a negative impact on urban life.…”
Section: Defining Key Themesmentioning
confidence: 99%